Nanosecond time-dependent Stokes shift at the tunnel mouth of haloalkane dehalogenases - Jesenská, Andrea; Sýkora, Jan; Olzyńska, Agnieszka; Brezovský, Jan; Zdráhal, Zbynek; Damborský, Jirí; Hof, Martin (Journal of the American Chemical Society, 2009)
The tunnel mouths are evolutionally the most variable regions in the structures of haloalkane dehalogenases originating from different bacterial species, suggesting their importance for adaptation of enzymes to various substrates. We decided to monitor the dynamics of this particular region by means of time-resolved fluorescence spectroscopy and molecular dynamic simulations. To label the enzyme specifically, we adapted a novel procedure that utilizes a coumarin dye containing a halide-hydrocarbon linker, which serves as a substrate for enzymatic reaction. The procedure leads to a coumarin dye covalently attached and specifically located in the tunnel mouth of the enzyme. In this manner, we stained two haloalkane dehalogenase mutants, DbjA-H280F and DhaA-H272F. The measurements of time-resolved fluorescence anisotropy, acrylamide quenching, and time-resolved emission spectra reveal differences in the polarity, accessibility and mobility of the dye and its microenvironment for both of the mutants. The obtained experimental data are consistent with the results obtained by molecular dynamics calculations and correlate with the anatomy of the tunnel mouths, which were proposed to have a strong impact on the catalytic activity and specificity of the examined mutants. Interestingly, the kinetics of the recorded time-dependent Stokes shift is unusual slow; it occurs on the nanosecond time-scale, suggesting that the protein dynamics is extremely slowed down at the region involved in the exchange of ligands between the active-site cavity and bulk solvent.
Keywords: Models, Molecular; Catalytic Domain; Spectrometry, Fluorescence; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; akrylamid; fluorescenční spektrometrie; kumariny; mutageneze cílená; molekulární modely; stochastické procesy; hydrolasy; Kinetics; Quantum Theory; fluorescenční barviva; anizotropie; Acrylamide; Coumarins; Fluorescent Dyes; spektrometrie hmotnostní - ionizace laserem za účasti matrice; kinetika; katalytická doména; kvantová teorie; Hydrolases; Mutagenesis, Site-Directed; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Anisotropy; Stochastic Processes